(untitled) (Universal International Scientific Journal, 2026)
This article considers pedagogical erudition as an important quality of a teacher, which embodies extensive knowledge, professional experience, scientific outlook and creative approach. The study scientifically analyzes its role in improving the quality and efficiency of education, its impact on the process of forming qualified specialists in the modern education system, as well as the prospects and existing problems of developing pedagogical erudition, and justifies the need to improve the professional competence of teachers.